Women’s Resistance in Cotton Industry: a Study of Ecological Destruction in East Sumba - Nugrohowardhani, R.L.K.R. (Yayasan Jurnal Perempuan, 2014)
National Cotton Acceleration Program (NCAP) being incepted in East Sumba since 2008 has created resistances among women farmers in Tanamanang Village. Forms of resistances are as follows: first they called the cotton as “project cotton” representing a symbolic resistance with negative connotation in speaking against the government project by reducing the existence of the word into “project”—no more no less. The second resistance is open-resistance in which they break the rules of planting-time, harvesting-time, and all the promises being signed before between the government and the farmers. The third resistance is by rejecting the program being incepted into their land. They openly say no to the planting of cotton in their front-back yard.